ADOPTION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) IN INDONESIA - Hamidah Hamidah (Universitas Hayam Wuruk Perbanas, 2013)
The IFRS can be applied in the multi national company (MNC) and listing firms across the countrybut it does not mean it can replace the national accounting standards that have been owned by respectivecountries. The accounting standardization is not an easy job because each country has differentpolitical, social, and economic background. This study is to reveal the reason and who is behindIFRS adoption in Indonesia. This qualitative research is a case study based on cases representinginstitutions in Indonesia: DSAK, DPN IAI, BAPEPAM-LK, the finance ministry and the ministryof state own enterprises (BUMN). Data were collected by interviews and using readily availabledocuments and processed with thematic analysis. The result shows the adoption of IFRS decisions isdriven by international interests. Indonesia's membership in several international organizations, suchas IFAC (International Federation on Accountant), IOSCO, and the G-20, has resulted in the approvalof global accounting standards in Indonesia. Each organization has done a variety ways toensure that its members adopt IFRS. IFRS should be based more on Indonesia accounting needs andshould not be only based on a desire particularly coercion from others. In-depth analysis based onthe reality of each particular business should be conducted before a decision to adopt IFRS is taken.